Surgeons, Manufacturers and Patients - Anderson, J. author. aut Link
XIV, 222 p.
Keywords: The Total Hip Replacement was invented by British surgeons after World War Two. It became the basis of a multi-billion global industry in joint replacement. This pioneering study ranges from inventive surgeons to multi-national manufacturers and explores total hip replacement in the very different health economies of the UK and the US.